2013
DOI: 10.1088/1674-1056/22/2/027104
|View full text |Cite
|
Sign up to set email alerts
|

Exchange couplings in magnetic films

Abstract: Recent advances in the study of exchange couplings in magnetic films are introduced. To provide a comprehensive understanding of exchange coupling, we have designed different bilayers, trilayers and multilayers, such as anisotropic hard-/soft-magnetic multilayer films, ferromagnetic/antiferromagnetic/ferromagnetic trilayers, [Pt/Co]/NiFe/NiO heterostructures, Co/NiO and Co/NiO/Fe trilayers on an anodic aluminum oxide (AAO) template. The exchange-coupling interaction between soft-and hard-magnetic phases, inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 107 publications
(195 reference statements)
0
19
0
Order By: Relevance
“…[10][11][12] It has been reported that the EB can be influenced by many factors in FM/ AFM system, such as the FM magnetization M FM , the thickness of FM layer t FM or AFM layer t AFM , and the anisotropy of AFM (K AFM ) or FM (K FM ). [2][3][4]13,14 The exchange bias field (H E ) is inversely proportional to the M FM and t FM , and the K AFM is reported to affect the critical thickness of the AFM layer. 2,3,15,16 Furthermore, the AFM or FM domain formation is also claimed to play a dominant role in EB.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[10][11][12] It has been reported that the EB can be influenced by many factors in FM/ AFM system, such as the FM magnetization M FM , the thickness of FM layer t FM or AFM layer t AFM , and the anisotropy of AFM (K AFM ) or FM (K FM ). [2][3][4]13,14 The exchange bias field (H E ) is inversely proportional to the M FM and t FM , and the K AFM is reported to affect the critical thickness of the AFM layer. 2,3,15,16 Furthermore, the AFM or FM domain formation is also claimed to play a dominant role in EB.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is found that the H E can be mediated by varying t FM , M FM , or K FM for different FM materials. [2][3][4] To search a FM material that exhibits a big change in K FM leading to a large variation of the H E within the narrow temperature range will be a very interesting issue.…”
Section: Introductionmentioning
confidence: 99%
“…Major progress of research on nanocomposite magnets in experiment was made in hard/soft multilayers. Zhang et al [6,18,19] added a non-magnetic layer between the soft magnetic layer and hard magnetic layer to enhance the coercivity of in hard/soft multilayers. Large energy product of 486 kJ/m 3 has been achieved in perpendicular anisotropic Nd 2 Fe 14 B/FeCo multilayers by Cui et al [20] in 2012.…”
Section: Introductionmentioning
confidence: 99%
“…After the first report of anti‐ferromagnetic coupling in Fe/Cr/Fe trilayer structures, the interlayer exchange coupling in ferromagnetic/non‐magnetic/ferromagnetic multilayer or nanoparticle systems has been widely investigated . Wang et al fabricate a kind of strongly magnetic, zero‐remanence nanoparticles with ferromagnetic multilayer structures (Figure d) .…”
Section: Examples Existing In Diverse Fields Support the Concept Of “mentioning
confidence: 99%